The future of value how sustainability creates value through competitive differentiation - Lowitt, Eric, 1972- (Jossey-Bass, 2011)
"Enhance business performance by using sustainability for competitive advantage. The Future of Value reveals what it takes for companies to grow and outperform the competition in today's growth-constrained, sustainability conscious world. The author shows leaders how to use sustainability as a powerful, pragmatic lens to enhance business performance. He also explores how to craft and oversee a portfolio of effective tools, develop competitive strategies, and adjust value chain activities, talent management practices, and corporate policies to help organizations execute powerful sustainability strategies. He provides a systematic, yet instantly familiar, model all companies can use to connect sustainability with their growth and competitive strategies. In this way, the author shows leaders how to shape, color, and own The Future of Value. Outlines the keys to implementing sustainability in organizations to achieve business success today and tomorrow Reveals how to engage stakeholders in day to day sustainability management as a means to shape and fuel efforts to continuously renew their sustainability strategies The author is a 15-year veteran of sustainability and strategy management consulting, having worked with clients in the US, Japan, Australia, and Europe. He has an MBA in Strategic Management from The University of Pennsylvania's Wharton School and writes a regular column for Sustainable Life Media and GreenBiz, two of the world's most heavily trafficked sustainability news and thought leadership portals The author draws useful and accessible conclusions from a rich, diverse set of corporate interviewees. A core part of his research was the selection and interrogation of more than 25 Global Fortune 500 companies' sustainability, strategy, and finance leads"--